Kehidupan Fanbase Twitter Nctzenhalu (Studi Korelasi antara Kesepian dan Hubungan Parasosial pada Dewasa Awal) - Ayu Dhaning Lestari; Hema Dayita Pohan (Merpsy Journal, 2023)
The wave of K-Pop can be found among various age groups around the world with easy access on social media in finding out information on his favorite idol figures. As a result of this sense of closeness, fans can use media figures as a substitute for social relationships in overcoming loneliness. This research aims to find out whether there is a correlation between loneliness and parasocial relationship. The convenience sampling method was used to select 151 respondents who followed the nctzenhalu on twitter for this research. The researcher used the parasocial relationship scale instrument based on the aspects proposed by Maltby et al. and the loneliness scale based on the aspects proposed by Weiss for this research. The analytical technique used in this research was the Spearman-Rho correlation test. The results of this research indicate that there is a positive relationship between loneliness and parasocial relationships in early adulthood, which means the greater the loneliness, the greater the parasocial relationship.